UJI KADAR FORMALIN PADA IKAN SEGAR YANG DIJUAL DI PASAR TEUPIN RAYA KECAMATAN GLUMPANG TIGA KABUPATEN PIDIE TAHUN 2020 - T. Khairol Razi; Fadli Syahputra; Fakhrurrazi Fakhrurrazi; Aswadi Aswadi (Jurnal Real Riset, 2022)
The use of formalin in fresh fish is triggered by the increase in production costs borne by fishermen due to the distance from fishing locations and the higher prices of diesel fuel and ice prices. the use of formalin, in addition to reducing the load, because fishermen do not have to bother carrying large quantities, production costs are estimated to be reduced by ±20% (BBRSE, 2005 in Hikmayani et al., 2007). This study aims to determine the content of formalin in fresh fish sold at the Teupin Raya Market, Glumpang Tiga District, Pidie Regency in 2020. This type of research is experimental research (laboratory test). The population in this study were all fish traders in the Teupin Raya market as many as 50 people. The purposive sampling method is the sampling method in this study by only taking fish samples from traders whose sales are still 5 fish traders, with the samples being shrimp (B1), milkfish (B2), mackerel (B3), and mackerel (B4). cob (K B1). The results of the study found that Formalin Levels in Fish Using the Colorimetric Method at Teupin Raya Market, Glumpang Tiga District, Pidie Regency in 2019/2020 with reference to the Merck method 1,08028.0001 the results of all samples of fish species were negative. Of the 5 fish samples taken from fish traders who continue to sell, the results showed that there were no positive formalin samples, while those with negative results were 5 samples with a percentage of 100%. The conclusion that the formalin content in fish using the colorimetric method with reference to the Merck method 1.08028.001, the results obtained were negative for all types of fish and the formalin content examination was also negative from 5 samples with a percentage of 100%. It is recommended for institutions to be expected to further improve the counseling process and provide direction on the use of good chemicals, for the community with this research the community can find out the impact of the use of formalin on foodstuffs such as noodles, fish, meatballs and others, and for students to identify chemicals which is dangerous with other methods besides the colorimetric method and can add insight to students.Keywords: Formalin, Fresh Fish